Abscisic acid influences tillering by modulation of strigolactones in barley - Wang, Hongwen; Chen, Wanxin; Eggert, Kai; Charnikhova, Tatsiana; Bouwmeester, Harro; Schweizer, Patrick; Hajirezaei, Mohammad R.; Seiler, Christiane; Sreenivasulu, Nese; von Wirén, Nicolaus; Kuhlmann, Markus (Oxford University Press, 2018)
Strigolactones (SLs) represent a class of plant hormones that are involved in inhibiting shoot branching and in promoting abiotic stress responses. There is evidence that the biosynthetic pathways of SLs and abscisic acid (ABA) are functionally connected. However, little is known about the mechanisms underlying the interaction of SLs and ABA, and the relevance of this interaction for shoot architecture. Based on sequence homology, four genes (HvD27, HvMAX1, HvCCD7, and HvCCD8) involved in SL biosynthesis were identified in barley and functionally verified by complementation of Arabidopsis mutants or by virus-induced gene silencing. To investigate the influence of ABA on SLs, two transgenic lines accumulating ABA as a result of RNAi-mediated down-regulation of HvABA 8’-hydroxylase 1 and 3 were employed. LC-MS/MS analysis confirmed higher ABA levels in root and stem base tissues in these transgenic lines. Both lines showed enhanced tiller formation and lower concentrations of 5-deoxystrigol in root exudates, which was detected for the first time as a naturally occurring SL in barley. Lower expression levels of HvD27, HvMAX1, HvCCD7, and HvCCD8 indicated that ABA suppresses SL biosynthesis, leading to enhanced tiller formation in barley.